Pengaruh Free Cash Flow Terhadap Nilai Perusahaan - Rezki Zurriah (Jurnal Riset Akuntansi dan Bisnis, 2021)
This study aims to examine the effect of free cash flow on firm value in basic industrial and chemical sector companies listed on the Indonesian stock exchange from 2016 to 2018. Sampling using the purposive sampling method, obtained 22 sample companies with a total observation of 66 units of analysis. Secondary data collection method with documentation study technique in the form of annual financial reports which are published on the website www.idx.co.id. The data analysis method in this study is simple linear regression where the results show that free cash flow has a positive and significant effect on firm value.